Arquitetura IIoT baseada em Apache Kafka para um sistema de alertas em máquinas industriais - Botêlho, Raul de Vasconcelos (2025)
Industry 4.0 is rapidly transforming the global manufacturing landscape by integrating cyber- physical systems, advanced automation, and real-time data analysis. In Brazil, this transformation is characterized by the flexibility of industries in adapting to new technologies, driven by the need for competitiveness in a global market. This study examines the application of emerging technologies in the field of Industrial Internet of Things (IIoT) with the goal of providing a flexible solution that enables the decentralization and digitalization of production workflows. Focusing on a footwear industry in northeastern Brazil, this case study explores how the adoption of these technologies is crucial for addressing the challenges of digital transformation and maintaining competitiveness. The proposed solution involves the use of Apache Kafka to enable continuous real-time alert flows and integration between Operational Technology (OT) and Information Technology (IT) systems. Using event-driven communication and flexible data formats such as JSON, the architecture aims to enhance the visibility and efficiency of industrial processes. Experimental results show that the system maintained latency below 300 ms under high-concurrency scenarios, with no data loss or duplication, representing a reduction of over 95% compared to the previous setup, which experienced delays of up to two minutes. This demonstrates the feasibility of the approach for critical applications in industrial environments. The proposed architecture proves to be a promising foundation for future expansions and integration with other Industry 4.0 technologies.